Job satisfaction and the reduction of non-quality costs.: Kondo's High Performance Cycle in the post-pandemic context. (AACINI - International Journal of Industrial Engineering, 2023)
The United Nations Industrial Development Organization (UNIDO) demonstrates, through the Competitive Industrial Performance Index (CIP), that the industrialization process is directly related to a better quality of life. Between 1996 and 2020, Argentina fell from 35th to 57th place among industrialized countries, and its CIP score dropped by 50.5%. Since productivity is one of the components of CIP, this paper identifies several factors that increase the value of CIP from the perspective of the High-Performance Cycle proposed by Yoshio Kondo. This model establishes the relationship between clear and challenging objectives, motivational factors, productivity, and non-quality costs. The research includes both field analysis and longitudinal studies of employee satisfaction in Argentina between 2016 and 2022. The first conclusion is that Kondo's High-Performance Cycle, validated in the cultural context of Argentina, shows the positive impact of improved explicit and challenging goal setting on both overall levels (34%) and job satisfaction. The model also shows the human side of quality, highlighting that quality has more to do with human nature than with methods and indicators. The cost of non-quality reduction (14%) leads to higher productivity, higher job satisfaction, and overall worker satisfaction. Finally, in terms of contributions to the field of human capital, the results not only confirm the Goal-Setting and Self-efficacy theories but also extend the High-Performance Cycle model proposed by Kondo. Postulating the presence of additional variables following research would allow for improving and adapting the predictive value of the model to different organizational contexts in Argentina.
Keywords: quality costs; satisfaction; motivation factors; High-Performance Cycle; Yoshio Kondo; human capital theory; sustainable development goals